Techniques for Developing a Product Line of Product Line Tools: A Comparative Study - Turnes, Lucineia; Bonifácio, Rodrigo; Alves, Vander; Lammel, Ralf (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS); 2011: Anais do V Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software, 2011)
Tool support is essential for Application Engineering in Software Product Lines (SPL). Despite a myriad of existing tools, most lack adequate support for flexibility and adaptability, so that it is hard for them to be applied in different contexts, e.g., addressing variability in different artifacts. Addressing this issue requires exploring underlying commonality and adequately managing variability of such tools. In order to provide systematic guidance in this direction, we have conducted a comparative analysis of variability management techniques for SPL tool development in the context of the SPL Hephaestus tool. The analysis reveals that two techniques, one annotative and another transformational, are most suitable to variability management in Hephaestus, and that their combination is a feasible strategy to improve such management.